Network of nanomedicine researches: impact of Iranian scientists - Mohammad-Hossein Biglu; Shukuh Riazi (BioImpacts, 2015)
Introduction: We may define the nanomedicine as the use of nanotechnology in the health care, disease diagnoses and treatment in order to maintain and increase the health status of a population through improve pharmacotherapy. The main objective of the current study is to analyze and visualize the co-authorship network of all papers in the field of nanomedicine published throughout 2002-2014 in journals and indexed in the Web of Science database. Methods: The Web of Science database was used to extract all papers indexed as a topic of nanomedicine through 2002-2014. The Science of Science Tool was used to map the co-authorship network of papers. Results: Total number of papers extracted from the Web of Science in the field of nanomedicine was 3092 through 2002-2014. Analysis of data showed that the research activities in the field of nanomedicine increased steadily through the period of study. USA, China, and India were the most prolific countries in the field. The dominant language of publications was English. The co-authorship connection revealed a network with a density of 0.0006. Conclusion: Nanomedicine researches have markedly been increased in Iran. Ninety-five percent of Iranian papers were cooperated with multi-authors. The collaboration coefficient degree was 0.731.